Working towards accountability in embedding Indigenous studies: Evidence from an Indigenous Graduate Attribute evaluation instrument. Issue 2 (August 2019) - Bodkin-Andrews, Gawaian; Page, Susan; Trudgett, Michelle
Whilst Indigenous Graduate Attributes – or the embedding Indigenous cultural competencies within broad graduate attributes – are becoming increasingly popular within some universities, it is essential that universities be held accountable for the realisation of such policies. Considering that Australian Indigenous Studies – an essential component of Indigenous Graduate Attributes – is a highly contested space where colonial and Indigenous knowledges collide, this article presents evidence from analyses, engaging with Indigenous Standpoints, aimed at evaluating critically the degree to which university subjects may contribute to the realisation of Indigenous Graduate Attributes. Results identify not only an array of psychometrically sound factors which measure Student Knowledges and Attitudes to Indigenous Issues as well as Applied Indigenous Learning, but also indicate that the embedding of Australian Indigenous Studies content may vary across disciplines. In addition, results show that the impact of such embedding on student attitudes also varies greatly according to discipline, with positive, negative, and contradicting results across disciplines. These findings strongly suggest that any commitment to embedding Indigenous Graduate Attributes must be monitored very carefully.